Simultaneously Monitoring Immune Response and Microbial Infections during Pregnancy through Plasma cfRNA Sequencing. (1st November 2017) - Pan, Wenying; Ngo, Thuy T M; Camunas-Soler, Joan; Song, Chun-Xiao; Kowarsky, Mark; Blumenfeld, Yair J; Wong, Ronald J; Shaw, Gary M; Stevenson, David K; Quake, Stephen R
Abstract: BACKGROUND: Plasma cell-free RNA (cfRNA) encompasses a broad spectrum of RNA species that can be derived from both human cells and microbes. Because cfRNA is fragmented and of low concentration, it has been challenging to profile its transcriptome using standard RNA-seq methods. METHODS: We assessed several recently developed RNA-seq methods on cfRNA samples. We then analyzed the dynamic changes of both the human transcriptome and the microbiome of plasma during pregnancy from 60 women. RESULTS: cfRNA reflects a well-orchestrated immune modulation during pregnancy: an up-regulation of antiinflammatory genes and an increased abundance of antimicrobial genes. We observed that the plasma microbiome remained relatively stable during pregnancy. The bacteria Ureaplasma shows an increased prevalence and increased abundance at postpartum, which is likely to be associated with postpartum infection. We demonstrated that cfRNA-seq can be used to monitor viral infections. We detected a number of human pathogens in our patients, including an undiagnosed patient with a high load of human parvovirus B19 virus (B19V), which is known to be a potential cause of complications in pregnancy. CONCLUSIONS: Plasma cfRNA-seq demonstrates the potential to simultaneously monitor immune response and microbial infections during pregnancy.